Progressive Consderation of Judges in Deciding Sentencing Under Indonesia New Criminal Code - Faisal, Faisal; Rahayu, Sri; Rahayu, Derita Prapti; Darmawan, Anri; Yanto, Andri (Faculty of Law, Jambi University, 2023)
The WvS Criminal Code of the Dutch colonial legacy does not formulate the objectives and guidelines of punishment in it, there are only rules for retaliatory criminal provision. The National Criminal Code has formulated explicitly the purpose and guidelines of punishment in it as a reference for judges in sentencing crimes. The purpose of this study is to analyze the basic idea of the objectives and guidelines of punishment which then the objectives and guidelines of the punishment will be a progressive consideration of judges in deciding the criminal conviction of criminal offenders. The research method used is normative legal research. The focus of the research analysis is on the concept of norms Article 51 to Article 54 of the National Criminal Code concerning the objectives and guidelines for punishment. Using the Law approach and analytical approach in explaining problems with the study of literature literature. The results of the study concluded that the basic idea of the purpose and guidelines of punishment is how criminal punishment can be humanist and in accordance with the values of Pancasila. There are at least 3 points that are considered as the basic idea of the goals and guidelines for punishment, namely uphold goals, strengthen principles and review guidelines. Furthermore, the purpose and guidelines of sentencing will be the affirmation and progressive consideration of the judge in sentencing the crime. Judges in enforcing the law become less rigid so that the balance between intellectual and spiritual intelligence plays an important role. Imposing crimes with a sense of humanity and justice. Punishment must contain humanitarian, educative and justice elements